Pelatihan Pembuatan Minyak Kelapa Murni (Virgin Coconut Oil) di Kecamatan Nekamese, Kabupaten Kupang - Dewi Lestarani; Arvinda C. Lalang; I Gusti N.Budiana; Jasman Jasman; Yantus A.B.Neolaka; Kasimir Sarifudin (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The Nekamese region has the potential for coconut trees that are traditionally converted into coconut oil. Traditional coconut oil is of poor quality in terms of health and requires a lot of energy to produce. While coconut can be processed into pure oil and when sold, it will be more expensive. One way to process virgin coconut oil is by fermentation. Such knowledge is exactly what the community needs. But the partners do not have knowledge about processing pure coconut oil. Therefore, the proposed solution for partners is to organize training on pure coconut oil production.